Clinical Comparison of Two Methods of Graft Preparation in Descemet Membrane Endothelial Keratoplasty. (2nd January 2018) - Rickmann, Annekatrin; Opitz, Natalia; Szurman, Peter; Boden, Karl Thomas; Jung, Sascha; Wahl, Silke; Haus, Arno; Damm, Lara-Jil; Januschowski, Kai
ABSTRACT: Purpose : Descemet membrane endothelial keratoplasty (DMEK) has been improved over the last decade. The aim of this study was to compare the clinical outcome of the recently introduced liquid bubble method compared to the standard manual preparation. Methods : This retrospective study evaluated the outcome of 200 patients after DMEK surgery using two different graft preparation techniques. Ninety-six DMEK were prepared by manual dissection and 104 by the novel liquid bubble technique. The mean follow-up time was 13.7 months (SD ± 8, range 6–36 months). Results : Best corrected mean visual acuity (BCVA) increased for all patients statistically significant from baseline 0.85 logMAR (SD ± 0.5) to 0.26 logMAR (SD ± 0.27) at the final follow-up (Wilcoxon, p = 0.001). Subgroup analyses of BCVA at the final follow-up between manual dissection and liquid bubble preparation showed no statistically significant difference (Mann–Whitney U Test, p = 0.64). The mean central corneal thickness was not statistically different (manual dissection: 539 µm, SD ± 68 µm and liquid bubble technique: 534 µm, SD ± 52 µm, ) between the two groups (Mann–Whitney U Test, p = 0.64). At the final follow-up, mean endothelial cell count of donor grafts was statistically not significant different at the final follow-up with 1761 cells/mm 2 (−30.7%, SD ± 352) for manual dissection compared to liquid bubble technique with 1749 cells/mm 2 (−29.9%, SD ± 501) (Mann–Whitney U-Test, p = 0.73). The re-DMEK rate was comparable for manual dissection with 8 cases (8.3%) and 7 cases (6.7%) for liquid bubble dissection ( p = 0.69, Chi-Square Test). Conclusion : Regarding the clinical outcome, we did not find a statistical significant difference between manual dissection and liquid bubble graft preparation. Both preparation techniques lead to an equivalent clinical outcome after DMEK surgery.